Wirefree Electrochemistry for Enhanced Detection and Treatment of Disease - Oisín Foley Doyle; Robert J. Forster (Electrochemistry Communications)
Wirefree, or bipolar electrochemistry, BPE, has the potential to transform patient outcomes through early diagnosis using ultrasensitive sensors for multiple biomarkers and personalised treatments such as enhanced cell growth, differentiation and destruction as well as local delivery of therapeutics. We highlight the emerging field of wirefree electroceuticals and show how BPE could enable precise modulation of neural circuits, non-pharmaceutical therapies for conditions like Parkinson’s disease and chronic pain management, as well as on-demand drug delivery with high spatial and temporal precision. Moreover, it explores the integration of advanced nanomaterials illustrating their pivotal role in enhancing electrode performance and biocompatibility, thereby maximising their potential diagnostic and therapeutic efficacy especially in vivo.